2009
DOI: 10.1007/s12225-009-9127-1
|View full text |Cite
|
Sign up to set email alerts
|

Three new species of Sarcocornia (Chenopodiaceae) from South Africa

Abstract: Sarcocornia decussata, S. freitagii and S. tegetaria from South Africa are described as new taxa. Sarcocornia decussata and S. freitagii are narrow endemics of the West Coast of South Africa where they are found in inland saline habitats (quartz patches, salt pans and saline alluvia) while S. tegetaria is an endemic of southern African coasts (spanning Namibia, South Africa and Mozambique) where it is confined to low-lying intertidal habitats of estuaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The Australian genera Halosarcia Paul G.Wilson, Pachycornia Hook.f., Sclerostegia Paul G.Wilson, and Tegicornia Paul G.Wilson were incorporated into one genus, Tecticornia Hook.f., by Shepherd & Wilson (2007). Several new taxa have recently been described especially in Sarcocornia A.J.Scott (Steffen & al., 2009;Fuente & al., 2011Fuente & al., , 2013Yaprak, 2012), Tecticornia (Shepherd, 2007a(Shepherd, , b, 2008Shepherd & Van Leeuwen, 2007Shepherd & Lyons;), Salicornia L. (Akhani, 2008;Yaprak & Yurdakulol, 2008) and Arthrocnemum Moq. (Sukhorukov & Nilova, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Australian genera Halosarcia Paul G.Wilson, Pachycornia Hook.f., Sclerostegia Paul G.Wilson, and Tegicornia Paul G.Wilson were incorporated into one genus, Tecticornia Hook.f., by Shepherd & Wilson (2007). Several new taxa have recently been described especially in Sarcocornia A.J.Scott (Steffen & al., 2009;Fuente & al., 2011Fuente & al., , 2013Yaprak, 2012), Tecticornia (Shepherd, 2007a(Shepherd, , b, 2008Shepherd & Van Leeuwen, 2007Shepherd & Lyons;), Salicornia L. (Akhani, 2008;Yaprak & Yurdakulol, 2008) and Arthrocnemum Moq. (Sukhorukov & Nilova, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…), embedded in a plain covered with undulating solidified dunes. This lineage grows in saline alluvia and salt pans and co‐occurs with yet another local endemic salicornid, Sarcocornia freitagii S. Steffen, Mucina & G.Kadereit (Steffen, Mucina & Kadereit, ), and (sub)halophytes, such as Cotula eckloniana (DC.) Levyns, Triglochin bulbosa L. subsp.…”
Section: Resultsmentioning
confidence: 99%
“…The apex of the segments was commonly used in the descriptions of some Sarcocornia species (Maire & Quézel, 1962;Castroviejo, 1990;Alonso & Crespo, 2008;Steffen & al., 2009Steffen & al., , 2010. Fuente & al.…”
Section: Discussionmentioning
confidence: 99%
“…As for previous morphological features, no tendency was newly observed between the studied species. Concerning to seed coat has been widely described for taxonomical purposes within the genus Sarcocornia (Shepherd & al., 2005;Alonso & Crespo, 2008;Steffen & al., 2009Steffen & al., , 2010, and specially to distinguish between S. fruticosa and S. perennis (Maire & Quézel, 1962;Meikle, 1977;Valdés & al., 1987b;Bolòs & Vigo, 1990;Castroviejo, 1990;Cabello 2011;Guilló & al., 2012). For S. fruticosa, the mentioned authors reported a seed ornamentation well characterised by the presence of short hairs, papillae or mamelons.…”
Section: Discussionmentioning
confidence: 99%